The Role of Recreational Sports on Stress Degradation in Adolescents - Rahmawati, Fajar Aulia; Yuliastrid, Dita; Pudjijuniarto, Pudjijuniarto; Susanto, Indra Hirmanwan (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
The condition known as stress degradation is when the relationship between an individual and their environment can result in a gap with pressures that originate from various situations with various biological, psychological, and social system resources of an individual that decline. With the emergence of various problems in the lives of adolescents, it will cause things that end in increased stress. The purpose of this quantitative description study is to determine the role of recreational sports on stress degradation in adolescents. The researcher conducted an analysis using an observational analytical research method using a cross-sectional study design with a total of 52 adolescents aged 11-21 years in Menganti District - Gresik. Data collection using the Depression Anxiety Stress Scale 42 questionnaire and a recreational sports activity questionnaire. After all the data has been collected, the results will be tabulated data presented in a table, then processed using SPSS software version 25 then analyzed using simple linear regression. The results showed that the level of stress showed that most of the study respondents were high at 48.1% while for moderate at 36.5%. For very high at 9.6%. For normal at 3.8% and for mild at 1.9%. Recreational sports activity shows that most of the research respondents are very high at 80.8% while for high it is 17.3% and for moderate it is 1.9%. The results of the study showed that the magnitude of the correlation or relationship (R) value is 0.212 which means that there is a relationship between recreational sports activity and decreased stress levels is weak. The results of the analysis obtained a determination coefficient (R Square) of 0.045 which means that the influence of the independent variable, namely recreational sports activity on the dependent variable, namely the level of adolescent stress, is 45%.